Spécificités techno-sémio-linguistiques des commentaires en ligne - Chafik Kherbache; Rima Aida Hassani (Multilinguales)
Our study falls within the field of discourse analysis, aiming to understand the functioning of the online comment production process through a techno-semio-linguistic approach, bridging the gap between the pre-digital and digital eras. These comments are produced by users who previously did not have the right to respond to televised media discourse and merely played the role of a passive viewers. We strive to highlight the characteristics of these secondary techno-discourses, navigating between web design elements and usage elements. The communication process leverages both human and non-human agents that contribute to discursive production in a digital environment. The results indicate that user’s comments on the web varies according to the content of posts disseminating political and media content, involving political and ideological stakes emanating from the web’s prescriptive norms.